The practice of cost benefit analysis in the transport sector: A Mexican perspective - Vladimir Ramírez Soberanis (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2010)
Mexico's public investment process is strengthened by an institutional framework that ensures that projects with a high social return are given preference. The Federal Law of Budget and Financial Responsibility establishes as prerequisite for federal investments the obligation to present a Cost-Benefit Analysis (CBA), and to get the Investment Unit approval. This paper describes the use of CBA for the social and economic evaluation of transport infrastructure in Mexico and is made from the point of view of the role of the Ministry of Finance's Investment Unit in the appraisal process.
Keywords: 330